Local Ecological Knowledge (LEK) on Fish Behavior Around Anchored FADs: the Case of Tuna Purse Seine and Ringnet Fishers from Southern Philippines - Macusi, Edison D.; Abreo, Neil Angelo S.; Babaran, Ricardo P. (Frontiers in Marine Science, 2017)
The Fishing Industry in the Philippines plays an important role in the food and employment need of Filipino fishers. By using anchored Fish Aggregating Devices (FADs or payao), the Philippine tuna fisheries was transformed into a million-dollar industry. Minimal studies on exploitation rates and fish behavior around anchored FADs hampered further understanding of this fishery practice. Studies on fish behavior using Local Ecological Knowledge (LEK) are good complement where data is limited. A study using semi-structured interview (n = 46) and three focus group discussions (n = 39 participants) to record fishers' knowledge and observations on the behavior of different fish species around anchored FADs was conducted. This particularly focused on attraction, retention, and departure behavior of fishes in identified FAD sites. Based on the fishers' knowledge, tuna schools are attracted to anchored FADs at 10 km distance. In anchored FADs, tuna form schools segregated by species and size. There was no relationship between the attraction distance and the reported school size and the various waiting times for fish to aggregate below the FADs. There was no variation between the species present at day or night time although fishers have reported a distinction of species found near the surface (0–10 m) and those found at other depths (11–20 m). Juvenile yellowfin tuna (Thunnus albacares), skipjack (Katsuwonus pelamis), and frigate and bullet tunas (Auxis spp.) are found to stay at 25–50 m from the FAD at a depth of >20 m. Adult oceanic tunas reside in deeper waters (75 m). The fish visual census produced similar results with the semi-structured interviews and FGDs but did not observe oceanic tunas at depths of 15–20 m in the anchored FADs examined.